Air Pollution Exposure and COVID-19 - Matthew A. Cole; Ceren Ozgen; Eric Strobl (Institute of Labor Economics (IZA), 2020)
In light of the existing preliminary evidence of a link between Covid-19 and poor air quality, which is largely based upon correlations, we estimate the relationship between long term air pollution exposure and Covid-19 in 355 municipalities in the Netherlands. Using detailed secondary and administrative data we find compelling evidence of a positive relationship between air pollution, and particularly PM2.5 concentrations, and Covid-19 cases, hospital admissions and deaths. This relationship persists after controlling for a wide range of explanatory variables. Our results indicate that a 1 μ/m3 increase in PM2.5 concentrations is associated with 9.4 more Covid-19 cases, 3.0 more hospital admissions, and 2.3 more deaths. The relationship between Covid-19 and air pollution withstands a number of sensitivity and robustness exercises including instrumenting pollution to mitigate potential endogeneity and modelling spatial spillovers using spatial econometric techniques.
Keywords: I21; I23; Q53; 330; COVID-19; air pollution; Netherlands; spatial spillovers